History of the Teaching Profession in Indonesia - Maspuroh; Nurahda Febriyanti; Nova Diana Sauqia; Vani Zakiyah (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The teaching profession in Indonesia has undergone various changes over time, from the traditional education system to a more structured modern system. During the colonial period, the teaching profession developed through educational institutions established by the Dutch government and missionaries. After independence, the teaching profession became an important part of national development, especially after the establishment of the Indonesian Teachers Association (PGRI). Along with the changing times, teachers are required to have higher professional competence and be able to adapt to technological developments in the world of education. In addition, the teacher certification policy implemented in the last few decades has also had a significant impact on improving the quality of education. This article will discuss the history of the teaching profession in Indonesia comprehensively, from the pre-independence period to the current digital era, and highlight the role of teachers in shaping a sustainable national education system.